Allelopathic potential of Lathyrus aphaca L. on seedling growth of Triticum aestivum L. - Akmal, Mohammad (Current Botany, 2025)
The allelopathic substances released into the environment from plants inhibit various physiological processes. These allelopathic secondary plant metabolites attract or repel and stimulate or poison other organisms. In the present investigation, the allelopathic potential of a common weed, Lathyrus aphaca, was studied on the seedling growth of wheat (Triticum aestivum L. cv. Dara). The seedling growth was monitored under the different dilutions of L. aphaca extract with water. Control seedlings were grown in distilled water only, i.e., without extract. It was found that the growth and biomass accumulation were significantly suppressed. The aqueous extract of L. aphaca was analyzed through LCMS and revealed the presence of several allelochemicals, viz. 2,4,6-tetrahydroxychalcone, 3-iodo-benzoic acid, p-coumaric acid, kynurenic acid, fumaric acid, sebacic acid, caffeic acid, and ferulic acid, proving the allelopathic potential of the weed.